Effects of reduced blood pressure dipping on the progression of chronic kidney disease in children - Li Huarong; Chen Chaoying; Tu Juan; Lin Tiantian; Wang Nannan (BMC Pediatrics)
Abstract Background Hypertension is a common complication of chronic kidney disease (CKD) in children. It is related to the progression of CKD. However, current guidelines for hypertension management in CKD patients mainly focus on managing patients with above-target blood pressure (BP). The effects of reduced nocturnal BP dipping on CKD progression in children are unclear. Methods This single-center, retrospective cohort study analyzed the clinical data of children with stage 2–5 non-dialysis CKD undergoing ambulatory BP monitoring. Clinical characteristics and laboratory parameters of children with and without hypertension and/or reduced nocturnal BP dipping were analyzed. Results Ninety-four children were included (median age: 10 years; interquartile range [IQR]: 6–12 years; males: 65 [69.1%]). The median estimated glomerular filtration rate (eGFR) was 41 ml/min/1.73 m2, and the median 24-h proteinuria level was 637 mg/24 h. There were 41 (43.6%) cases of ambulatory BP at target and 53 (56.4%) cases of ambulatory hypertension. Nocturnal dipping without ambulatory hypertension was found in 10 cases (10.6%), nocturnal non-dipping without ambulatory hypertension in 31 cases (33.0%), nocturnal dipping with ambulatory hypertension in 5 cases (5.3%), and nocturnal non-dipping with ambulatory hypertension in 48 cases (51.1%). The nocturnal non-dipping with ambulatory hypertension group had the lowest hemoglobin level (F = 2.798, P = 0.045), eGFR (F = 3.228, P = 0.026), and 25 (OH) D3 level (F = 3.428, P = 0.023). During a 15-month median follow-up (IQR: 7–31 months), 27 patients (28.7%) showed a decrease in eGFR of > 3 ml/min/1.73m2/year. Further, 21 patients (22.3%) progressed to end-stage kidney disease requiring kidney replacement therapy. The nocturnal non-dipping with ambulatory hypertension group had the highest renal progression risk (hazard ratio [HR] = 3.634; 95% confidence interval [CI], 0.866–15.258), while the nocturnal dipping with ambulatory hypertension group (HR = 1.945; 95% CI, 0.273–13.865) had similar risks to the nocturnal non-dipping without ambulatory hypertension group (HR = 1.584; 95% CI, 0.350–7.171). Multivariate Cox regression analysis revealed that persistent proteinuria and reduced nocturnal BP dipping were associated with renal outcomes. Conclusion Regardless of whether ambulatory BP was normal, reduced BP dipping was correlated with the risk of renal progression in children with CKD.